Africa Centres for Disease Control and Prevention's framework for antimicrobial resistance control in Africa - Jay K. Varma; John Oppong-Otoo; Pascale Ondoa; Olga Perovic; Benjamin J. Park; Ramanan Laxminarayan; Rosanna W. Peeling; Constance Schultsz; Han Li; Chikwe Ihekweazu; Amadou A. Sall; Baboucarr Jaw; et al. (AOSIS, 2018)
No abstract available.